Remitting seronegative symmetrical synovitis with pitting edema syndrome in individuals with type 2 diabetes mellitus or impaired glucose tolerance. Issue 1 (October 2015) - Oyama, Kohta; Taniguchi, Jun-ichi; Goto, Rieko; Matsui, Kunihiko
Highlights: An association between remitting seronegative symmetrical synovitis with pitting edema (RS3PE) syndrome and insulin or dipeptidyl peptidase-4 (DPP4) inhibitor therapy was previously reported. We report four cases of RS3PE syndrome with type 2 diabetes mellitus or impaired glucose tolerance (IGT) without insulin or DPP4 inhibitor medication. RS3PE syndrome might be associated with diabetes, regardless of type or anti-diabetes therapies. Abstract: An association between remitting seronegative symmetrical synovitis with pitting edema (RS3PE) syndrome and insulin or dipeptidyl peptidase-4 (DPP4) inhibitor therapy were previously reported. We encountered four cases of RS3PE syndrome with type 2 diabetes mellitus or impaired glucose tolerance (IGT) without insulin or DPP4 inhibitor medication.